Dietary factors associated with being overweight and obese among school-going adolescents in Region One, The Gambia - Tunkara-Bah, Haddy (Heliyon, 2021)
BACKGROUND: The purpose of this study was to determine the dietary factors associated with being overweight and obese among school-going adolescents in Region One, The Gambia. METHOD: This was a school-based cross-sectional study and 1008 students from eight Senior Secondary Schools in Region one of The Gambia participated in it. Data were collected through questionnaire self-administered method, and weight and height measurements. Using the age and gender-specific cutoff points proposed by World Health Organization, body mass index (BMI) was calculated using the weight and height measures. The data were analyzed using frequencies for underweight, overweight, and obesity, and the association between dietary factors and weight status of participants was determined using the Chi-square test. FINDINGS: Out of the 1008 students recruited in the study, 981 of them completed and returned the questionnaires, resulting in a total response rate of 97%. The mean age of the participants was 17.3 years (SD = 1.9) and 385 of them (39.2%) were from grade 10. There were 627 (63.9%) females. The mean BMI for all the students was 20.0 ± 3.4 kg/m(2). Most of the students (n = 672; 68.5 %) had normal body weight, but 226 (23%), 76 (7.7 %) and 7 (0.7%) of them were underweight, overweight and obese respectively. There was a significantly higher number of female students who were overweight (n = 64, 10.2%) than their male counterparts (χ(2) = 72.336, p < 0.001). The frequency of drinking sugar added juices and full cream milk, eating fish, shrimps, oysters, lobsters, and snacks such as cakes and biscuits were significantly associated with overweight and obesity among the participants (p < 0.05). In conclusion, the problem of under-nutrition and over-nutrition co-existed among the students which were associated with poor eating habits.